2017
DOI: 10.1080/0167482x.2017.1396313
|View full text |Cite
|
Sign up to set email alerts
|

Being a donor-child: wishes for parental support, peer support and counseling

Abstract: Peer support and counseling by professionals for donor-conceived offspring should be available for those who need it. The findings also support professional counseling for intended parents before treatment to improve parental support for donor-children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Early disclosure of conception is associated with a higher relationship quality with parents ( Blake et al , 2014 ; Schrijvers et al , 2019 ), and donor-conceived offspring expressed the view that prospective parents should have counselling before treatment to prepare for disclosure so that parents could talk more openly about donor conception ( Schrijvers et al , 2019 ). More information on disclosure is described above ( Information for recipients ).…”
Section: Recommendations For Information Provision and Support For Do...mentioning
confidence: 99%
See 2 more Smart Citations
“…Early disclosure of conception is associated with a higher relationship quality with parents ( Blake et al , 2014 ; Schrijvers et al , 2019 ), and donor-conceived offspring expressed the view that prospective parents should have counselling before treatment to prepare for disclosure so that parents could talk more openly about donor conception ( Schrijvers et al , 2019 ). More information on disclosure is described above ( Information for recipients ).…”
Section: Recommendations For Information Provision and Support For Do...mentioning
confidence: 99%
“…Donor-conceived offspring can search for donors and same-donor offspring through the MAR centre/gamete bank, direct-to-consumer genetic testing websites, or through registries set up for this purpose. The existence of these organizations seems to be beneficial for some donor-conceived offspring, with positive feedback on searching and knowing that there are others in a similar situation to exchange experiences with ( van den Akker et al , 2015 ; Schrijvers et al , 2019 ). Others (estimated at 30%) did not want to have peer contact ( Schrijvers et al , 2019 ).…”
Section: Recommendations For Information Provision and Support For Do...mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have asked adults that were donor‐conceived about their experiences learning of their conception. Donor‐conceived persons wished their parents had spoken more openly about using donor gametes and missed getting support from their parents around donor issues (Schrijvers et al, 2019). They also discussed being aware of when their parents felt uncomfortable or ashamed of infertility and using donor gametes, making open discussion more difficult.…”
Section: Emotional Aspects Of Third‐party Reproductionmentioning
confidence: 99%
“…Published children's books targeting the lay audience and aiming to explain to children about conception by gamete donation (eggs or sperm) are available in several languages, including English and in Swedish. However, a study of donor-conceived children found that these children wished that their parents had received counselling about how to talk with the child about donor conception at several stages during the child's life [17]. It is reasonable to believe that many solo-mothers by choice will turn to a primary healthcare provider for advice regarding disclosure issues.…”
Section: Discussionmentioning
confidence: 99%